NEW OFFER FROM PT SAFARI DHARMA SAKTIENDLESS SUMMER TOUR - Bella Christy Nathania Effendy; Anthony Sanjaya; Sonia Rest Wulandari; Katherine Meyers; Justin J. Kannalayil; Fatmah J S GH Alqedhaibi; Nourah A H H M Almutairi (International Journal of Applied Business and International Management, 2018)
PT Safari Dharma Sakti is a company engaged in transportation services. Vehicles that this company has has an international standard compared to other transportation service companies. Even in terms of service, PT Safari Dharma Sakti is also sufficient. But this company only moves in local tourists only, therefore Team 10 offers to be a consultant and help it to Go International to be known not only local tourists but also from abroad. Team 10 gets a lot of information from interviews ranging from price to promotion what has been used. Our team performs with the PIC of the company that is Mr. Samuel and discuss many things. Finally our group gave suggestions to organize tours provided by the company's own team. And the company team was very agree, interested, and expect a lot of this "Endless Summer Tour" plan.